Effect of embryo cryopreservation before surgery on clinical outcomes in IVF patients with endometrioma - Nozomi Takahashi; Yuma Kawahara; Miyuki Harada; Tomoko Makabe; Gentaro Izumi; Osamu Wada‐Hiraike; Yasushi Hirota; Yutaka Osuga (Reproductive Medicine and Biology)
Abstract Purpose This study evaluated whether embryo cryopreservation before surgery (ECBS) improves clinical outcomes in in vitro fertilization (IVF) patients with endometrioma. Methods This retrospective study included patients aged 28–42 years with endometrioma who underwent oocyte retrieval at our hospital from 2019 to 2022. Seventeen patients who underwent ECBS and 43 patients who underwent embryo transfer (ET) without surgery were included. Patient characteristics, reproductive outcomes, and obstetric outcomes were compared between the groups. Results Maximum cyst size was significantly larger in the ECBS group than in the control group. The abortion rate per pregnancy was significantly lower (0% vs. 35.5%) in the ECBS group than in the control group. The ongoing pregnancy rate per case was significantly higher in the ECBS group than in the control group (88.2% vs. 58.1%), while the time to ongoing pregnancy was similar. Among patients in the ECBS group who experienced live births, 84.6% became pregnant following three or fewer ET attempts. Multivariate analysis revealed that ECBS was the only factor associated with ongoing pregnancy. The rates of perinatal complications are comparable between the groups. Conclusions ECBS is an effective method to improve reproductive outcomes in IVF patients with endometrioma without prolonging the time to pregnancy.